Do Medical Comorbidities Affect Outcomes in Patients With Rotator Cuff Tears?. Issue 8 (21st August 2017) - Gagnier, Joel J.; Allen, Benjamin; Watson, Scott; Robbins, Christopher B.; Bedi, Asheesh; Carpenter, James E.; Miller, Bruce S.
Background: The effects of medical comorbidities on clinical outcomes in patients with rotator cuff tears (RCTs) have not been fully elucidated. This study investigates the association between medical comorbidities, as measured by the Functional Comorbidity Index (FCI), and clinical outcomes in patients treated surgically or nonsurgically for symptomatic, full-thickness RCTs. Hypothesis: Patients with RCTs who have more comorbidities will have worse outcome scores. Study Design: Cohort study; Level of evidence, 3. Methods: We collected the following outcome measures at baseline and at regular intervals up to 64 weeks in all patients: FCI, the Western Ontario Rotator Cuff Index (WORC), and the American Shoulder and Elbow Surgeons (ASES) score. Changes in outcomes were compared separately for surgical and nonsurgical patients using paired t tests. The relationship of the FCI and all outcomes of interest at baseline, at 64-week follow-up, and for changes from baseline was explored using linear regression modeling. Results: Of the 222 study patients (133 males; mean age, 60.0 ± 9.6 years), 140 completed the 64-week WORC and 120 completed the 64-week ASES. Overall, 128 patients underwent RCT repair, and 94 patients were treated nonsurgically. Both treatment groups improved compared with baseline at 64 weeks on the ASES score and WORC. At 64 weeks, patients with higher baseline FCI scores had worse WORC score (by 74.5 points; P = .025) and ASES score (by 3.8 points; P < .01). A higher FCI score showed a trend toward predicting changes in the WORC and ASES scores at 64 weeks compared with baseline, but this did not reach statistical significance (WORC change, P = .15; ASES change, P = .07). Conclusion: Patients with higher FCI scores at baseline reported worse baseline functional scores and demonstrated less improvement with time. The magnitude of this change may not be clinically significant for single comorbidities.